Thermal studies on protein isolates of white lupin seeds (Lupinus albus) - Fontanari, Gustavo Guadagnucci [UNESP]; Martins, Jose Manuel; Kobelnik, Marcelo; Pastre, Ieda Aparecida [UNESP]; Gomes Areas, Jose Alfredo; Batistuti, José Paschoal [UNESP]; Fertonani, Fernando Luís [UNESP] (Springer, 2012)
This study used TG, DSC, and SDS-PAGE techniques to study protein isolates (PIs) in the powder form obtained from lupin seeds flour Lupinus albus. Different methods of preparing PIs were tested, resulting in final products that were different only in relation to the yield and protein content. The results of the protein analysis by SDS-PAGE showed that the same protein fractions were present in the lupin seeds and in the obtained PIs. This result shows that the process of extraction was not damaging to the composition of the original protein. on the other hand, the results of the thermal analysis (DSC and TG-DTG curves) obtained for the different PIs, led to the detection of changes in the protein conformation through the Delta H values, which in general decreased with increasing values of pH and ionic strength in the experimental conditions of extraction.
Keywords: Lupinus albus; TG; DSC; Protein isolate; SDS-PAGE